2022
DOI: 10.1111/gcb.16455
|View full text |Cite
|
Sign up to set email alerts
|

Tropical surface temperature response to vegetation cover changes and the role of drylands

Abstract: Vegetation's effect on the surface energy balance remains an open question due to its competing influences on land surface temperature (Shen et al., 2015). It is essential to determine vegetation's net effect on the energy balance given ongoing global land cover changes, including deforestation, agricultural expansion, climate changeinduced greening, and replanting efforts (Alkama et al., 2022;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 119 publications
2
9
0
Order By: Relevance
“…In contrast, albedo is significantly lower in GRE than in CTL, with larger albedo differences in the northwest of the plateau. The lower albedo difference in the southeast of the plateau can be explained by the saturation of the albedo response to vegetation changes in the regions with higher values of vegetation fraction (Figure S3 in Supporting Information ; Feldman et al., 2023). Such spatial patterns of changes in growing season surface properties over the plateau since 2001 are overall consistent with those in previous studies (Ge et al., 2020; Tian et al., 2022; B. Q. Zhang et al., 2021).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, albedo is significantly lower in GRE than in CTL, with larger albedo differences in the northwest of the plateau. The lower albedo difference in the southeast of the plateau can be explained by the saturation of the albedo response to vegetation changes in the regions with higher values of vegetation fraction (Figure S3 in Supporting Information ; Feldman et al., 2023). Such spatial patterns of changes in growing season surface properties over the plateau since 2001 are overall consistent with those in previous studies (Ge et al., 2020; Tian et al., 2022; B. Q. Zhang et al., 2021).…”
Section: Methodsmentioning
confidence: 99%
“…In thermal risk landscapes, reductions in vegetation cover in urban ecosystems were found to be due to exposure to extreme thermal events or prolonged hot weather, and thus ESV may be reduced by anomalous changes in MET (Kabano et al, 2021). Feldman et al (Feldman et al, 2023) explained the negative effects of heat stress in terms of plant surface cooling capacity. In addition, this study also investigated the interactions between ESV drivers (ECO, MET and LULC).…”
Section: Impact Pathways Of the Esvmentioning
confidence: 99%
“…Based on this, Froehlich modified it to adapt it to site‐specific under‐cloud atmospheric conditions and to observe long‐term seasonal variations in excess deuterium (Froehlich et al, 2008), suggesting that secondary evaporation under clouds is a local factor influencing stable isotope variations in precipitation. Recent studies have concluded that topographic features (Chen et al, 2021; Feldman et al, 2023; Huang et al, 2021) have a significant impact on under‐cloud evaporation, which is more intense in the plains than in the mountains (Chen et al, 2020; Zhu et al, 2021). Stable isotopes in central and eastern Asia are affected by below‐cloud evaporation, especially in the arid regions of central Asia and the northern Tibetan Plateau (Wei et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have concluded that topographic features (Chen et al, 2021;Feldman et al, 2023;Huang et al, 2021) have a significant impact on under-cloud evaporation, which is more intense in the plains than in the mountains (Chen et al, 2020;Zhu et al, 2021).…”
mentioning
confidence: 99%